Quantum decoherence - Vrbica, Mile (Matrika, 2019)
In this article the the process of environment-induced quantum decoherence will be studied from the perspective of quantum-to-classical transition. The formalism of density operators will be briefly introduced. Methods for finding states that are minimally influenced by the interaction with environment will be mentioned and loss of certain quantum properties in open systems explained. Some real-world experiments and examples will be given, among which the commonly encountered example of decoherence due to scattering will be described in more detail.
Keywords: kvantna dekoherenca; kvantna mehanika; quantum decoherence; quantum mechanics